Indoor use of essential oil-based cleaning products: Emission rate and indoor air quality impact assessment based on a realistic application methodology. (1st February 2021) - Angulo Milhem, S.; Verriele, M.; Nicolas, M.; Thevenet, F.
Abstract: Cleaning is performed to increase hygiene, esthetics and material preservation. Despite its benefits, cleaning also poses risks, potentially contributing to nearly 20% of indoor pollution. As indoor air quality has become a major human health concern, "natural-scented" cleaning products, formulated with essential oils, have become market leaders among household products. However, these consumer products have benefitted from skillful marketing strategies based on the ambiguity of the words "green" and "natural". The characterization of the emission processes studied through 1-m 3 chamber experiments under a realistic scenario suggests variable maximum total terpene concentrations from 150 to 300 ppb. The estimated emission rate profiles confirm that the liquid-to-gas transfer of terpenes is driven by (i) the formulation of the product matrix inducing specific chemical affinities, (ii) the liquid content of individual terpenes, and (iii) the intrinsic volatility of terpenes. A unique formaldehyde emission kinetics profile was observed, suggesting the presence of a unique emission source: formaldehyde-releasers. Consequently, the use of essential-oil-based cleaning products might generate a long-term increase in the indoor formaldehyde concentration, and the maximum levels might be sustained for several hours after cleaning. Thus, essential-oil-based cleaners should be seriously considered as versatile and significant sources of fragrance molecules and formaldehyde. Graphical abstract: Image 1 Highlights: Quantitative determination of terpenoid VOC emissions from cleaning products. Investigation of the temporal dynamic of terpene emissions under realistic scenarios. Environmental evaluation of the impact of cleaning products on indoor air quality.